Change in Postprandial Level of Remnant Cholesterol After a Daily Breakfast in Chinese Patients With Hypertension - Xu, Jin; Qu, Peiliu; Du, Xiao; Xiang, Qunyan; Guo, Liling; Zhu, Liyuan; Tan, Yangrong; Fu, Yan; Wen, Tie; Liu, Ling (Frontiers in Cardiovascular Medicine, 2021)
Background: Hypertension(HBP) is usually accompanied by hypertriglyceridemia that represents the increased triglyceride-rich lipoproteins(TRLs) and cholesterol content in remnant lipoproteins (i.e. remnant cholesterol, RC). According to the European Atherosclerosis Society(EAS), high RC(HRC) is defined as fasting RC ≥ 0.8 mmol/L or/and postprandial RC ≥ 0.9 mmol/L. However, little was known about postprandial change in RC level after a daily meal in Chinese patients with HBP. Methods: One hundred and thirty-five subjects, including 90 hypertensive patients(HBP group) and 45 non-HBP controls(CON group), were recruited in this study. Serum levels of blood lipids, including calculated RC, were explored at 0, 2 h, and 4 h after a daily breakfast. Receiver operating characteristic(ROC) curve analysis was used to determine the cut-off point of postprandial HRC. Results: Fasting TG and RC levels were significantly higher in HBP group(P＜0.05), both of which increased significantly after a daily meal in two groups(P＜0.05). Moreover, postprandial RC level was significantly higher in HBP group(P＜0.05). ROC curve analysis showed that the optimal cut-off point for RC after a daily meal to predict HRC in corresponding to fasting RC 0.8 mmol/L was 0.91 mmol/L, which was very close to that recommended by the EAS, i.e. 0.9 mmol/L. Fasting HRC was found in 31.1% hypertensive patients but not in the controls. According to the postprandial cut-off point, postprandial HRC was found in about half of hypertensive patients and about one third of the controls. Conclusion: Postprandial RC level increased significantly after a daily meal and hypertensive patients had higher percentage of HRC at both fasting and postprandial states. More importantly, the detection of postprandial lipids could be helpful to find HRC.